PENGARUH KEAKTIFAN BERORGANISASI, TEMAN SEBAYA DAN KESIAPAN BELAJAR TERHADAP INDEKS PRESTASI KUMULATIF MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Mela Oktasari (Universitas Negeri Padang, 2018)
The purpose of this research is to know the influence of activation of organization, peer group, and readiness of study toward students’ achievement at economic education faculty of padang state university . The type of the research is descriptive asosiative. The primary data obtained through the distribution of questionnaires to the student . The population in this study are the students at economic education at academic year 2014, 2015 and 2016 . The sample of this research were 78 students, thay were chosen by using slovin technique. The results of this study indicate that: (1) there is a significant influence between activation organization, peer group and readiness of study toward students’ achievement at economic education faculty of padang state university .(2) there is a positive and significant influence between activation organization toward students’ achievement at economic education faculty of padang state university (3) there is a positive and significant influence between peer group toward students’ achievement at economic education faculty of padang state university (4) there is a positive and significant influence between readiness of study toward students’ achievement at economic education faculty of padang state university Key words : learning achievement (IPK), activation organization, peer group and readiness of study